2005
DOI: 10.1038/sj.bjc.6602423
|View full text |Cite
|
Sign up to set email alerts
|

Patient motivations surrounding participation in phase I and phase II clinical trials of cancer chemotherapy

Abstract: Successful advances in the treatment of advanced malignant diseases rely on recruitment of patients into clinical trials of novel agents. However, there is a genuine concern for the welfare of individual patients. The aim of this study was to examine motives of patients entering early clinical trials of novel cancer therapies. Questionnaire survey with both open- and close-ended questions. The patients were surveyed after they had given informed consent and before or during the first cycle of treatment. In all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
120
2
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(133 citation statements)
references
References 25 publications
6
120
2
5
Order By: Relevance
“…In fact, when patients in the current study were asked during a follow-up phone interview about factors that played a role in treatment decisions, 45% said that physician recommendations were a major factor, and another 35% said that physician recommendations were somewhat of a factor. This finding also supports previous studies demonstrating that physician behavior influences patient decisions regarding clinical trials [5,6,14,15,22]. Daugherty et al [15] found that many patients who participated in Phase I clinical trials were motivated by trust in their oncologist and in the institution.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…In fact, when patients in the current study were asked during a follow-up phone interview about factors that played a role in treatment decisions, 45% said that physician recommendations were a major factor, and another 35% said that physician recommendations were somewhat of a factor. This finding also supports previous studies demonstrating that physician behavior influences patient decisions regarding clinical trials [5,6,14,15,22]. Daugherty et al [15] found that many patients who participated in Phase I clinical trials were motivated by trust in their oncologist and in the institution.…”
Section: Discussionsupporting
confidence: 80%
“…Research indicates that oncologists' recommendations may indeed influence patients' decision to participate in a clinical trial [5,14,15,22]. However, existing empirical research to inform this debate is lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kanskje de trenger mindre paternalistisk beskyttelse enn vi er vant med å tro. Noen empiriske undersøkelser viser at pasienter er motivert til å delta fordi det kan gi direkte fordeler hva angår deres egen helse, men også fordi det kan bidra til å hjelpe andre og til økt kunnskap (5,6). Betaling kan vaere en tilleggsmotivasjon for å delta, men langt fra avgjørende hvis betalingen er moderat og standardisert (7).…”
unclassified
“…A significant body of literature has explored the motivations, hopes, and expectations of healthy volunteers and patients who participate in various clinical trials, including fih trials [19][20][21][22][23][24][25] . Patient-related factors influencing the decision about whether to participate in fih trials include unmet need for treatment options, lived illness experience, suffering and impact on quality of life, willingness to accept higher risks in the hope that the experimental treatment might provide at least symptom relief if not cure, and familiarity with and understanding of clinical trials and investigational molecules.…”
Section: Introductionmentioning
confidence: 99%